Clinical overlap between progressive supranuclear palsy (PSP) and frontotemporal dementia (FTD) in an elderly patient with earlier depression and psychosis - Md. Rosli , Ahmad Nabil; Razali, Rosdinom; Mohamed Ibrahim, Norlinah; Sahathevan, Ramesh (Elsevier B.V., 2015)
Overlapping of symptoms frequently occur in progressive supranuclear palsy (PSP), frontotemporal dementia (FLD) and corticobasal degeneration (CBD). Apathy, behavioral changes, cognitive impairment, prominent parkinsonism, impaired mobility and falls are ‘‘classical’’ features of this clinical spectrum of taupathies, with no definite disease-modifying treatment